O USO DA NISTATINA COMO AUXILIAR NO ISOLAMENTO DE BACTÃ‰RIAS DO SOLO - Neder, R. N.; Camargo, R. de; Martinelli Fo., A.; Falanghe, H. (REVISTA DE AGRICULTURA, 2015)
O USO DA NISTATINA COMO AUXILIAR NO ISOLAMENTO DE BACTÃ‰RIAS DO SOLO